Experimental Results on Preparation and Drying of Carrots - Latifovich, Khudayberdiev Tokhirjon; Askarali kizi, Toshpulatova Dilafruz (American Journal of Biodiversity, 2025)
The article presents the results of experiments on the preparation of carrots and the convection drying mode. The technological scheme of production of dried carrots and quality analysis are considered.